Chemokines and Chemokine Receptors in Multiple Sclerosis - Wenjing Cheng; Guangjie Chen (Mediators of Inflammation)
Multiple sclerosis is an autoimmune disease with classical traits of demyelination, axonal damage, and neurodegeneration. The migration of autoimmune T cells and macrophages from blood to central nervous system as well as the destruction of blood brain barrier are thought to be the major processes in the development of this disease. Chemokines, which are small peptide mediators, can attract pathogenic cells to the sites of inflammation. Each helper T cell subset expresses different chemokine receptors so as to exert their different functions in the pathogenesis of MS. Recently published results have shown that the levels of some chemokines and chemokine receptors are increased in blood and cerebrospinal fluid of MS patients. This review describes the advanced researches on the role of chemokines and chemokine receptors in the development of MS and discusses the potential therapy of this disease targeting the chemokine network.